Rational Action and Networking Strategy of Small Fisherman’s Household - Retna Mutiar, Indria; Sumarti, Titik; Satria, Arif (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2018)
ABSTRACTPoverty still occurs among the fishermen community. Climate changes, uncertainty of catch, and capital limitations, became a problem experienced by fishermen. Social network is one of the adaptation strategy of fishermen. The function of the social network not only to social relations, but also there are economical motives. The choice of fishermen in networking is a rational action. According to Weber’s view, there are four types rational action, such as instrumental/practice rational action, theoretical rational action, substantive rational actions, and formal rational action. But, in this study, only found one rational action, such as instrumental rational action. This study aims to analyzed the rational action of small fishermen in networking. The study uses a mixed-method that combine qualitative and quantitative approach. The subjects of this research were 65 small fishermen obtained from the poor households. The result shows that the social network in the small fishing community of Karangsong has three types, such as (1) social network based on sea activities, (2) social network based on the social relation type, and (3) social network based on the strong weakness of ties. Meanwhile, the rational action of fishermen in forming a social network is an instrumental rationality.Keyword: Social Network, Fisherman’s Poverty, Fisherman Community, Adaptation Strategy, Rational ActionABSTRAKKemiskinan masih terjadi di kalangan masyarakat nelayan. Perubahan iklim, ketidakpastian hasil tangkap, dan keterbatasan modal, menjadi masalah yang dialami nelayan. Jaringan sosial merupakan salah salah satu strategi adaptasi yang dilakukan nelayan. Fungsi dari jaringan sosial tersebut, yaitu bukan hanya sebatas hubungan sosial, tetapi juga terdapat motif-motif ekonomi di dalamnya. Pilihan nelayan dalam berjejaring merupakan tindakan yang bersifat rasional. Tindakan rasional sendiri terdiri dari beberapa tipe. Menurut pandangan Weber, terdapat empat tipe tindakan rasional, yaitu tindakan rasional instrumental/praktik, tindakan rasional teoritis, tindakan rasional substantif, dan tindakan rasional formal. Tetapi, di dalam studi ini hanya menemukan satu tipe tindakan rasional, yaitu tindakan rasional instrumental. Studi ini bertujuan untuk menganalisis tindakan rasional nelayan kecil Karangsong dalam berjejaring. Metode penelitian ini menggunakan pendekatan kualitatif dan kuantitatif. Adapun responden di dalam penelitian ini yaitu berjumlah 65 nelayan kecil yang didapatkan dari data Rumah Tangga Miskin (RTM) sasaran. Hasil dari penelitian ini menunjukkan bahwa jaringan sosial yang dibentuk oleh nelayan kecil Karangsong yaitu; (1) Jaringan sosial berdasarkan aktivitas melaut, (2) Jaringan sosial berdasarkan tipe hubungan sosial, dan (3) Jaringan sosial berdasarkan kuat lemahnya ikatan. Sementara itu, tindakan rasional nelayan dalam membentuk suatu jaringan sosial merupakan tindakan rasionalitas instrumental.Kata kunci: Jaringan Sosial, Kemiskinan Nelayan, Masyarakat Nelayan, Strategi Adaptasi, Tindakan Rasional